Molecular Genetics Mutations of Retinoblastoma - Mutia Arnisa Putri (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Retinoblastoma is a cancer that arises because both copies of the RB1 gene that normally suppresses retinoblastoma are lost from a developing retinal cell in fetuses, babies, and young children. Retinoblastoma is the prototype genetic cancer in one or both eyes of young children, most retinoblastomas are initiated by biallelic mutation of the retinoblastoma tumor suppressor gene, RB1, in a developing retinal cell. All those with bilateral retinoblastoma have heritable cancer, although 95% have not inherited the RB1 mutation. Nonheritable retinoblastoma is always unilateral, with 98% caused by loss of both RB1 alleles from the tumor, whereas 2% have normal RB1 in tumors initiated by amplification of the MYCN oncogene. A rare subset of retinoblastoma is initiated by somatic amplification of the MYCN oncogene in a predisposing retinal cell. The retinoblastoma protein (pRB), encoded by RB1, is an important transcription factor.